A Reevaluation of Cryolava Flow Evolution: Assumptions, Physical Properties, and Conceptualization. Issue 1 (28th December 2022) - Morrison, Aaron A.; Whittington, Alan G.; Mitchell, Karl L.
Abstract: Cryovolcanism has been invoked to explain numerous features observed on icy bodies. Many of these features show similar morphologies to volcanic features observed on Earth suggesting similar physics involved in their formation. Cryovolcanism lies at the intersection of volcanology and hydrology but as such, no one model from either discipline satisfactorily represents cryolava flow emplacement. We produced a new model for cryolava flow evolution that draws from both disciplines to track the physical, chemical, and thermal states of a hypothetical H2 O‐NaCl flow on a Europa‐like body as it evolves away from the vent. This model is currently restricted to compositions on the water‐rich side of this chemical system and only predicts emplacement up to the turbulent to laminar transition. Modeling the laminar regime and a broader compositional space will be dealt with separately. Concentrations between 5 and 23 wt% (H2 O‐NaCl eutectic) and initial flow thicknesses of 0.1, 1, 10, and 100 m were set as initial conditions. Model results suggest that flow may reach 40–60 vol% solids before transitioning to laminar flow. The thermal budget for these flows is dominated by the heat loss from vaporization in the low‐pressure environment. This model produces length to thickness aspect ratios, for the given compositions, that are broadly consistent with candidate cryovolcanic features on Ceres and Titan. These first‐order comparisons are not ideal and suggest the need for future modeling of cryovolcanic features in at least two dimensions. Plain Language Summary: Cryovolcanism is the icy volcanism that may occur on the surface icy bodies in the outer solar system. Erupted material will be predominantly aqueous fluid indicating that cryovolcanism lies at the intersection of volcanology and hydrology. However, neither discipline has models that adequately account for all of the parameters necessary for a cryovolcanic context. We produced a model for cryolava flow evolution that draws from both disciplines to track the physical, chemical, and thermal state of a hypothetical H2 O‐NaCl flow. Results suggest that these flows may evolve more like a slush rather than a river with an expanding ice cap. These flows may also begin crystallizing while still in the turbulent regime. The transition to laminar flow may therefore be important to constrain, as it could be a point where a morphology or surface expression changes due to changing in behavior in the flow. Extending this model to different compositions and allowing more complicated mixtures may help to draw comparisons to observations of surface flows on icy satellites. Key Points: Reynolds and Stokes number suggest turbulence and particle entrainment may persist to crystal contents >60% Heat loss due to vaporization is the largest heat flux in this context, accounting for >95% of the total thermal budget The "life" of a cryolava flow (expressed as distance traveled) may be predominantly in the turbulent regime, whereas a silicate lava flow would be predominantly laminar